2014
DOI: 10.1016/j.aca.2014.03.030
|View full text |Cite
|
Sign up to set email alerts
|

Multi-response optimization of the extraction and derivatization protocol of selected polar metabolites from apple fruit tissue for GC–MS analysis

Abstract: Given the complexity of the plant metabolome exhibiting a wide spectrum of physico-chemical properties, finding the best compromise for GC-MS analysis is a challenging exercise. In this study, the GC-MS protocol for extracting and analyzing polar metabolites from apple tissue is optimized. We found pure methanol extraction to be slightly better as compared to the two phase methanol/chloroform/water extraction in terms of introducing less degradation of the extracted metabolites while being comparable in extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 35 publications
2
10
0
Order By: Relevance
“…Extraction and derivatization of polar metabolites were performed following the protocols described by Bekele et al ( 2014 ). The frozen hypanthium tissue samples were homogenized using Mixer Mill (Retsch, MM 200, Haan, Germany) at a frequency of 30 Hz for 1 min.…”
Section: Methodsmentioning
confidence: 99%
“…Extraction and derivatization of polar metabolites were performed following the protocols described by Bekele et al ( 2014 ). The frozen hypanthium tissue samples were homogenized using Mixer Mill (Retsch, MM 200, Haan, Germany) at a frequency of 30 Hz for 1 min.…”
Section: Methodsmentioning
confidence: 99%
“…As the reaction time was prolonged, the signal response of organic acid derivatives remained constant. Similarly, Elias and co-authors found that long term silylation-derivatization process was beneficial to stearic acid and glucose-6-phosphate [ 25 ]. Therefore, the derivatization reaction between MTBSTFA and organic acids was carried out for 90 min at 130 °C.…”
Section: Resultsmentioning
confidence: 99%
“…This is in line with the findings of Koek, who showed that organic acids and sugars need relatively low volumes of the silylating agent [ 27 ]. It could be explained as molecular interaction because the reactivity of TMS groups is low to oxygen in organic acids, having a lower number of unshared electrons, higher steric hindrance, and transition state energy [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Response surface methodology (RSM) including the Box-Behnken design (BBD) and central composite design (CCD), is a mathematical and statistical tool for assessing the effect of variables on a response, which is the preferred way to find the best compromising set of parameters in sample preparation [31]. A number of algorithms have been developed, such as Khuri-Conlon approach, quality loss function and desirability function [32]. Among them, the desirability function is the most widely used methodology for simultaneously optimizing multiple variables.…”
Section: Multi-response Optimization Of Cgo/pvc Spe Proceduresmentioning
confidence: 99%